New Liquid Crystal Assemblies Based on Cyano-Hydrogen Bonding Interactions - Hagar, Mohamed; Ahmed, Hoda A.; Alnoman, Rua B.; Jaremko, Mariusz; Emwas, Abdul-Hamid; Sioud, Salim; Abu Al-Ola, Khulood A. (Frontiers in Chemistry, 2021)
A new selection of supramolecular liquid crystal complexes based on complementary molecules formed via hydrogen-bonding interactions is reported. All prepared complexes were prepared from 4-n-alkoxybenzoic acid (An) and N-4-cyanobenzylidene-4-n-(hexyloxy)benzenamine (I). FT-IR, temperature gradient NMR, Mass Spectrometer and Chromatography spectroscopy were carried out to confirm the -CN and −COOH H-bonded complexation by observing their Fermi-bands and the effects of the 1H-NMR signals as well as its elution signal from HPLC. Moreover, binary phase diagrams were established for further confirmation. All formed complexes (I/An) were studied by the use of differential scanning calorimetry and their phase properties were validated through the use of polarized optical microscopy Results of mesomorphic characterization revealed that all presented complexes exhibited enantiotropic mesophases and their type was dependent on the terminal lengths of alkoxy chains. Also, the mesomorphic temperature ranges decreased in the order I/A6 > I/A8 > I/A10 > I/A16 with linear dependency on the chain length. Finally, the density functional theory computational modeling has been carried out to explain the experimental findings. The relation between the dimensional parameters was established to show the effect of the aspect ratio on the mesophase range and stability. The normalized entropy of the clearing transitions (∆S/R) was calculated to illustrate the molecular interaction enhancements with the chain lengths.